Contribution of paramedical services costs in health expenditures of Iranian households: The study period 2011 to 2015 - Jafar Yahyavi Dizaj; Sara Emamgholipuor Dashti; Faroogh na'emani; Reza Reza hashempuor (Tehran University of Medical Sciences, 2020)
Background & Aims of study: Hospital care and paramedical services has become one of the most important and problematic issues in the field of health and critical concern of health planners and policymakers. In current study, contribution of various paramedical services costs were extracted from the total household health expenditure. Materials and Methods: The current study is a descriptive study that was conducted in a 5-year study period from 2011 to 2015. The annual income-based survey data of the household provided by Statistics Center during 2011-2015 was used to achieve the study aims. Excel_2013 software was used. Contribution of household and paramedical services cost were calculated from household health expenditures per year in urban and rural areas. Results: Regarding the results of the current study, on average, 20 % of total household health expenditure is allocated to paramedical services in urban and rural areas. The cost of radiology, sonography, radiotherapy, scan, echo cardiac stress test, endoscopy, electrocardiogram (ECG) etc, accounts for the largest contribution of hospital and non-hospital paramedical services costs, which include an averagely about 50 %t of paramedical services costs. Conclusion: Understanding paramedical services costs can guide policymakers and decision-makers in the field of paramedical services to decide better. Moreover it helps them to reduce direct payments from the pocket of household health expenditures. Therefore, considering the laboratory sector and radiology, sonography, radiotherapy sectors and so on are very important to reduce paramedical services costs.